Kelayakan Usahatani Padi Varietas Unggul Baru di Sawah Tadah Hujan Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Maya Dhania Sari; Harnisah Harnisah; Suparwoto Suparwoto (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Dhania Sari et al, 2017. Farm System Feasibility of New Prime Variaty in Rained Rice Field in Ogan Komering Ilir Regency South Sumatera Province. JLSO 6(2):120-125.Economic feasibility is farmers’ main consideration in implementing technology innovation in their rice farming business. The increase of farmers’ revenue can be obtained through the production improvement, and through the use of New Prime Variety which is one of the technology component that is able to increase rice production. Rainfed rice field in Ogan Komering Ilir (‘OKI’) Regency which covers 9,397 hectares is potential for further production optimality. This study aims to understand the revenue of rice farming business through the use of New Prime Variety in Rainfed Rice Field, and also to understand financial feasibility of New Prime Variety rice farming business in OKI Regency. The study method was undertaken by Plot Demonstration in Cahya Maju Village, Lempuing Sub District, OKI Regency in April - June 2016 for 2 hectares area. The data consists of primary and secondary data. The technology was implemented with Inpari 15, Inpari 20, Inpari 22, Inpari 27, Inpari 29, Inpari 30 Variety, and with Ciherang Variety as a comparison and also with the integrated plant management. The data analysis method is using tabulation and financial analysis. The study result shows that Inpari Variety has the highest financial gain with IDR 31,254,000. Economic wise, all varieties are financially feasibile, which is shown by the R/C ratio > 1.